2010
DOI: 10.1186/1750-2187-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Zinc release from thapsigargin/IP3-sensitive stores in cultured cortical neurons

Abstract: BackgroundChanges in ionic concentration have a fundamental effect on numerous physiological processes. For example, IP3-gated thapsigargin sensitive intracellular calcium (Ca2+) storage provides a source of the ion for many cellular signaling events. Less is known about the dynamics of other intracellular ions. The present study investigated the intracellular source of zinc (Zn2+) that has been reported to play a role in cell signaling.ResultsIn primary cultured cortical cells (neurons) labeled with intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 45 publications
(41 reference statements)
2
42
1
Order By: Relevance
“…It is IP 3 that mobilized Ca 2+ from ER to cytosol by binding and activating its specific receptors (IP 3 Rs) localized on the ER membranes (Stork and Li, 2010). Therefore, elevated levels of IP 3 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is IP 3 that mobilized Ca 2+ from ER to cytosol by binding and activating its specific receptors (IP 3 Rs) localized on the ER membranes (Stork and Li, 2010). Therefore, elevated levels of IP 3 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using fluorescent probes with 0.7 nM dissociation constant for zinc have shown that ER, Golgi, and mitochondria likely have higher concentrations of free zinc (Tomat et al 2008;Stork and Li 2010;Burdette et al 2001). Thus it is plausible for zinc to modulate adiponectin oligomerization in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The drawing does not imply that all three pathways operate in the same cell. Zinc signaling events among cytoplasm, nucleus, and mitochondria are not shown Biometals (2011) 24:411-418 413 released from an ER store that is thapsigargin/IP 3 -sensitive as is typical for calcium release from this store (Stork and Li 2010). The IP 3 -pathway is also triggered by zinc ion binding to GPR39, an orphan G-protein-coupled receptor (Sharir et al 2010).…”
Section: Generating Free Zinc Ionsmentioning
confidence: 99%